EXPLORING INTERVENTION FOR WIDOWS IN BINGA DISTRICT, ZIMBABWE: A SOCIAL WORK INTEGRATIVE MODEL - Misheck Dube (Stellenbosch University, 2021)
This article discusses a social work intervention model that addresses the psychosocial plight of widows in Zimbabwe. The ARTICLE uses a qualitative approach and a phenomenological research design as a basis for one-on-one interviews, focus group discussions, and key informant interviews that provided the information needed for the formulation of a social work basic care integrative model. The findings of the research indicate that there are gaps in social work interventions that suggest the need for an integrative intervention model to guide social workers in practice in meeting the welfare needs of the widows in Binga District.